2017
DOI: 10.1515/biol-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates oxidative stress in liver in Type 1 diabetic rats

Abstract: Abstract:We investigated the effect of curcumin on liver anti-oxidative stress in the type 1 diabetic rat model induced by streptozotocin (STZ). Experimental diabetic rats were induced by STZ intraperitoneally. All rats were fed for 21 days including three groups of control (NC), diabetic model (DC) and curcumin-treated (Cur, 1.5 g/kg by gavage). The results showed that curcumin-treatment significantly decreased the blood glucose and plasma malondialdehyde levels, but significantly increased the plasma superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The phytochemical curcumin is a free radical scavenger and hydrogen donor and exhibits both pro-oxidant and antioxidant activity. In the experimental diabetic rats induced by streptozotocin (STZ), the effect of curcumin on liver antioxidative stress showed inhibition of polyol pathway associated with down-regulated expression of protein kinase C (PKC) and poly ADP ribose polymerase (PARP) in the curcumin-treated group compared with the diabetic model (Xie et al, 2017). Curcumin directly reacts and scavenge reactive oxygen species (such as superoxide anion, hydroxyl radicals, hydrogen peroxide, singlet oxygen, nitric oxide, peroxynitrite and peroxyl radicals).…”
Section: Curcuminmentioning
confidence: 99%
“…The phytochemical curcumin is a free radical scavenger and hydrogen donor and exhibits both pro-oxidant and antioxidant activity. In the experimental diabetic rats induced by streptozotocin (STZ), the effect of curcumin on liver antioxidative stress showed inhibition of polyol pathway associated with down-regulated expression of protein kinase C (PKC) and poly ADP ribose polymerase (PARP) in the curcumin-treated group compared with the diabetic model (Xie et al, 2017). Curcumin directly reacts and scavenge reactive oxygen species (such as superoxide anion, hydroxyl radicals, hydrogen peroxide, singlet oxygen, nitric oxide, peroxynitrite and peroxyl radicals).…”
Section: Curcuminmentioning
confidence: 99%
“…This is because sorbitol (which is the substrate of SDH) is generated by the activity of reductase. Xie et al [ 43 ] showed that plasma SDH and AR, as well as the activities of the enzymes in the liver increased in the diabetic group. Khorsand et al [ 44 ] demonstrated that Mel prevented STZ‐induced hyperglycemia by decreasing blood glucose and HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%